The Risks of Sexual and Reproductive Activity on the Occurrence of Cervical Cancer in Central Sulawesi Province: Case Study of patients of Undata Hospital - Dilla Srikandi Syahadat; Ni Made Eviyulianti; Muh. Jusman Rau; Elvaria Mantao; Sendhy Krisnasari (Journal of Health and Nutrition Research, 2022)
This study aimed to determine the risk of age at first having sexual intercourse, parity, use of hormonal contraception, and exposure to cigarette smoke for the incidence of cervical cancer in Undata Hospital. This type of research was a quantitative method with a case-control approach. Case samples were 48 people, and control samples were 48 people with matching ages. Sampling was done by purposive sampling. The data source used secondary data from medical record records for 2021-2022 and primary data obtained through interviews with questionnaires. Data analysis used the odds ratio test, and the results showed that age at first sexual intercourse (OR= 2.333; CI = 1.029-5.292), parity (OR= 4.000; CI = 1.712-9.346), use of hormonal contraception (OR= 2.600; CI = 1.130-5.984), and exposure to cigarette smoke (OR= 1.486; CI = 0.539-4.100), are risk factors for cervical cancer. To overcome the incidence of cervical cancer, women of childbearing age and sexually active are expected to be routinely screened by doing pap HPV smear and vaccination